Changes in serum vitamin B12 levels in patients with megaloblastic anaemia treated with folic acid. Issue 3 (May 1962) - Johnson, S.; Swaminathan, S. P.; Baker, S. J.
Abstract : In 21 patients with megaloblastic anaemia associated with the tropical malabsorption syndrome serum vitamin B12 levels have been measured serially before and during parenteral folic acid therapy. In 11 patients there was a significant rise in serum B12 levels, reaching a peak three to 17 days after starting the folic acid. In three of these cases, absorption of labelled B12 was the same before and after the administration of folic acid. In two cases there was a fall in serum B12 levels and in seven there was no change. In one case small amounts of folic acid produced no change in serum B12 levels, whereas larger doses produced a prompt but transient rise.